A comparative study of efficacy of intramuscular PGF2alpha and intramuscular oxytocin in management of third stage of labour - Agarwal, Manju; Meena, Saroj Kumari; Sushma, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The third stage of labour is most crutial stage begins with expulsion of baby and end with expulsion of placenta and membranes. The present study was conducted to evaluate the scope of using prophylactic intramuscular carboprost tromethamine in comparison with intramuscular oxytocin for active management of third stage of labor. Methods: Patients were divided randomly into 2 groups 39 in each group. Patients assigned to group 1 received 10 units oxytocin IM and group 2 received carboprost 125 µg IM after delivery of anterior shoulder of baby. The main outcomes measured were duration of third stage of labor, mean amount of blood loss, additional oxytocic requirement, HB changes in group and side effects of drug which were used in each group. Results: Subjects who received carboprost showed a significant reduction in duration of third stage of labor (P= 0.041), amount of blood loss (P=0.046) and requirement of additional oxytocic compared to the subject who received oxytocin 10 units. Conclusions: Carboprost 125µg is better alternative compared to injection 10 units oxytocin in the prophylactic management of third stage of labor.